2014
DOI: 10.1186/s12870-014-0307-2
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing reveals early, dynamic transcriptome changes in the corollas of pollinated petunias

Abstract: BackgroundPollination reduces flower longevity in many angiosperms by accelerating corolla senescence. This response requires hormone signaling between the floral organs and results in the degradation of macromolecules and organelles within the petals to allow for nutrient remobilization to developing seeds. To investigate early pollination-induced changes in petal gene expression, we utilized high-throughput sequencing to identify transcripts that were differentially expressed between corollas of pollinated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 101 publications
1
40
0
Order By: Relevance
“…Flower senescence is genetically determined, and it can be accelerated by pollination. Several petunia ATG genes have been identified and reported to be regulated during pollinationinduced flower senescence (Broderick et al, 2014;Shibuya et al, 2013). We found that PhATG4, PhATG5, PhATG6, PhATG7, PhATG8a, and PhATG13 were also upregulated during the age-induced senescence of unpollinated flowers (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Flower senescence is genetically determined, and it can be accelerated by pollination. Several petunia ATG genes have been identified and reported to be regulated during pollinationinduced flower senescence (Broderick et al, 2014;Shibuya et al, 2013). We found that PhATG4, PhATG5, PhATG6, PhATG7, PhATG8a, and PhATG13 were also upregulated during the age-induced senescence of unpollinated flowers (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…x Primers were designed for this manuscript using cDNA sequences identified by Broderick et al (2014). with 0.5°C increments every 5 s).…”
Section: Gene Namementioning
confidence: 99%
See 3 more Smart Citations